Routines of Common Experience. The Spinozian Artist as Producer (ALPHA. Journal of Arts, Literature and Philosophy, 2020)
The present work explores the status of art in the philosophy of Spinoza (aspect scarcely studied by critics), within the framework of the Copernican revolution that gives rise to aesthetics (the “secondary qualities” are not qualities of objects but effects in the subjects who perceive) and the Dutch Baroque. Although the Spinozist thought is inscribed in the anthropological conversion by virtue of which beauty turns out to be an effect on the subject and not a property of objects, its understanding of art is unassimilable to "aesthetics" as a differentiated and autonomous area that it was consolidated in the eighteenth century, and rather conceived art integrated to life and common experience –at the same time, as praxis of bodily origin within the reach of anyone, presents points of contact with the historical avant-gardes of the twentieth century–. Spinoza conceives the production of "artworks" less as an aesthetic fact than as a body activity ethically oriented to the good life.
Keywords: Spinoza; art; esthetic; baroque; body